2014
DOI: 10.1007/s00411-014-0576-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling age-dependent radiation-induced second cancer risks and estimation of mutation rate: an evolutionary approach

Abstract: Although the survival rate of cancer patients has significantly increased due to advances in anti-cancer therapeutics, one of the major side effects of these therapies, particularly radiotherapy, is the potential manifestation of radiation-induced secondary malignancies. In this work, a novel evolutionary stochastic model is introduced that couples short-term formalism (during radiotherapy) and long-term formalism (post treatment). This framework is used to estimate the risks of second cancer as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is also important to note that due to the higher survival rate of cancer patients in recent years, the risk to develop radiation induced second tumours has now become of greater importance than ever [23]. It was recently shown that the frequency of micronuclei can be predictive of the cancer risk, which suggests that higher amounts of genetic damage after irradiation is correlated with early events in carcinogenesis [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that due to the higher survival rate of cancer patients in recent years, the risk to develop radiation induced second tumours has now become of greater importance than ever [23]. It was recently shown that the frequency of micronuclei can be predictive of the cancer risk, which suggests that higher amounts of genetic damage after irradiation is correlated with early events in carcinogenesis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Various theoretical models for radiation-induced cancer have been developed with model parameters fitted to clinical data. [1][2][3][4][5][6][7][8][9][10][11][12] Recent studies [16][17][18][19] have applied the S-model 8,10 to estimate the outcome of different treatment modalities with regard to radiation-induced cancer. Based on assumptions on cell repopulation/repair, mutation, and sterilization, the S-model gives a dose dependent formulation for the excess absolute risk (EAR).…”
Section: Methodsmentioning
confidence: 99%
“…Phenomenological risk models are frequently applied to estimate the risk of radiation-induced cancers at radiotherapy doses. [1][2][3][4][5][6][7][8][9][10][11][12] From the analysis of the Hiroshima and Nagasaki atomicbomb (A-bomb) survivors, it is known that solid cancer risk per unit dose varies significantly with both age at exposure and attained age. 13,14 Any realistic model of radiation-induced cancer at radiotherapy doses should therefore include the age dependence of risk.…”
Section: Introductionmentioning
confidence: 99%